Evaluasi Penggunaan Aplikasi Ninja Driver di Ninja Xpress Jasinga Bogor Menggunakan PIECES Framework - Awaliyah, Rita; Rusmanto; Wibowo, Edi (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The growth of e-commerce in Indonesia has driven the need for fast and ef icient delivery services, including Ninja Xpress,which utilizes the Ninja Driver application to support courier operations. This study aims to evaluate the Ninja Driverapplication at Ninja Xpress Jasinga using the PIECES framework (Performance, Information, Control, Ef iciency, Service).The research employed a quantitative approach through questionnaires distributed to 27 couriers as respondents,complemented by interviews with the company to validate the findings. The results showed average scores for Performance(2.74), Information (3.15), Control (3.27), Ef iciency (3.10), and Service (3.07), with all aspects rated as "agree." Theapplication supports ef iciency and service, such as reducing delivery time and improving the quality of information.However, there are issues with application stability in weak signal areas and delays in the validation process. Overall, theapplication is considered adequate in supporting courier operations but requires improvements in stability and ef iciencyfeatures. Recommendations include enhancing application stability in areas with weak signals, improving the delivery statusvalidation mechanism for faster processing, and developing error-handling features.